J02 A global development program testing RG6042, an anti-sense oligonucleotide, for the treatment of early manifest huntington's disease (hd). (September 2018) - Schobel, Scott; Palermo, Giuseppe; Trundell, Dylan; Kremer, Thomas; Sanwald-Ducray, Patricia; Smith, Anne; Boak, Lauren; Doody, Rachelle; ,
Abstract : Background: RG6042 (formerly IONIS-HTTRx) is a non-allele-specific, huntingtin mRNA-targeting antisense oligonucleotide which reversibly suppresses production of all forms of Huntingtin protein (HTT). In a first-in-human test of this approach, RG6042 safely lowered the pathogenic mutant HTT (mHTT) in early Huntington's disease (HD) patients, prompting Roche to begin a Global Development Program. Questions to be answered in the next phase of development include: what is the ultimate sustained magnitude of lowering of mHTT that can be achieved over long-term dosing; will lowering of mHTT be associated with clinical benefit and what are the best ways to measure such benefit; and will the approach prove to be safe and well tolerated over longer-term dosing? Method/results: This Global Development Program includes a single, pivotal, 24-month efficacy study designed to demonstrate clinical efficacy and safety of RG6042 in early manifest HD patients, and examine the effects on slowing or stopping clinical progression of HD. The program also includes an ongoing, open-label extension study of the completed Phase I/IIa study (NCT03342053 ), and an observational natural history study, both being conducted in a limited number of sites. The rationale for the target population, pivotal study design, endpoints and digital monitoring tools will be discussed. Conclusion: The Roche Global Development Program will provide valuable information on the clinical benefit and safety of the huntingtin lowering treatment RG6042 for patients with HD, as well as further longitudinal evidence of the causal role of mHTT in disease progression.